1996
DOI: 10.1111/j.1532-5415.1996.tb01442.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Regional Variability in the Surgical Treatment of Cancer Among Older People

Abstract: Although older people remain less likely to receive surgical therapy than younger persons, for some important cancer sites the gap between the treatment of older and younger individuals narrowed from 1973 through 1991.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several studies have reported that elderly women diagnosed with breast carcinoma consistently receive less aggressive treatment for their disease 1–14. This conservative therapeutic attitude could be justified on several grounds.…”
mentioning
confidence: 99%
“…Several studies have reported that elderly women diagnosed with breast carcinoma consistently receive less aggressive treatment for their disease 1–14. This conservative therapeutic attitude could be justified on several grounds.…”
mentioning
confidence: 99%
“…The reasons for this phenomenon include, among others, a higher level of co-morbidity, which may affect treatment choices, and which has been shown to be of prognostic relevance [20] (although co-morbidity should affect relative survival rates much less than absolute survival rates), less favourable stage distribution, and less aggressive treatment among older patients (independently of comorbidity) [21,22]. For example, it has been shown that older cancer patients are less likely to be referred to specialist care [23], and to receive definitive therapy, such as surgical treatment [24], chemotherapy [25] or radiation [21] than younger patients. Furthermore, differences in tumor biology and aggressiveness are also likely to play a role for some forms of cancer [26,27].…”
Section: Discussionmentioning
confidence: 96%
“…2 Encouragingly, there seems to be a trend for increased surgical treatment and survival of elderly patients in recent years. 15…”
Section: Treatmentmentioning
confidence: 99%